Restoration of exocrine pancreatic function in older children with cystic fibrosis on ivacaftor. (September 2020) - Nichols, A.L.; Davies, J.C.; Jones, D.; Carr, S.B.
Abstract: Prior to the use of cystic fibrosis (CF) modulator therapy, exocrine pancreatic insufficiency in CF was thought to be irreversible. Improvement in pancreatic function on ivacaftor has been reported in open label studies in 1–5 year olds. The mechanism by which ivacaftor might improve exocrine pancreatic function is unclear. Although the effect of ivacaftor on pancreatic function may be more significant in younger children, evidence is mounting that there may still be potential for improvement in older children on long term therapy.